Optimization for HTTP Adaptive Video Streaming in UAV-Enabled Relaying System - Hu, Han; Zhan, Cheng; An, Jianping; Wen, Yonggang (IEEE International Conference on Communications (2003), 2019)
To guarantee quality of experience (QoE) of video streaming for ground users with large obstacles that deteriorate the quality of links, unmanned aerial vehicle (UAV) is introduced in this paper as a relay to serve these users for HTTP adaptive streaming. By introducing the QoE utility model for users, we study the average QoE maximization problem in UAV-enabled relaying system by optimizing the UAV position along with the bandwidth and transmit power allocation for ground users, subject to the information causality constraint at the UAV relay. The optimization problem is formulated with a non-convex programming which is difficult to solve in general. By applying the successive convex approximation and block coordinate descent techniques, an efficient iterative algorithm is proposed to simultaneously update the UAV's position, transmit power and bandwidth allocation at each iteration, where the convergence is analyzed. Extensive simulations are conducted to show that the proposed solution can achieve significant gains for QoE in terms of the average streaming utility.